2021
DOI: 10.3390/coatings11060671
|View full text |Cite
|
Sign up to set email alerts
|

Moisture-Assisted Formation of High-Quality Silver Nanowire Transparent Conductive Films with Low Junction Resistance

Abstract: Silver nanowire (AgNWs) transparent conductive film (TCF) is considered to be the most favorable material to replace indium tin oxide (ITO) as the next-generation transparent conductive film. However, the disadvantages of AgNWs, such as easy oxidation and high wire-wire junction resistance, dramatically limit its commercial application. In this paper, moisture treatment was adopted, and water was dripped on the surface of AgNWs film or breathed on the surface so that the surface was covered with a layer of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Silver-based materials have been important in the scientific field in recent years [ 16 , 17 ]. As reported, silver nanowires (AgNW) are considered to be a favorable material to replace ITO because of their high conductivity, high transparency, suitability for printing, and flexibility [ 15 , 18 , 19 ]. At present, AgNW-based TCFs can be fabricated through conventional preparation techniques, such as vacuum filtration [ 20 ], spin-coating [ 21 , 22 ], drop coating [ 23 ], spray-coating [ 24 ], Mayer rod coating [ 25 , 26 ], and screen printing [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silver-based materials have been important in the scientific field in recent years [ 16 , 17 ]. As reported, silver nanowires (AgNW) are considered to be a favorable material to replace ITO because of their high conductivity, high transparency, suitability for printing, and flexibility [ 15 , 18 , 19 ]. At present, AgNW-based TCFs can be fabricated through conventional preparation techniques, such as vacuum filtration [ 20 ], spin-coating [ 21 , 22 ], drop coating [ 23 ], spray-coating [ 24 ], Mayer rod coating [ 25 , 26 ], and screen printing [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the requirement of flexible stretchability was achieved in mechanical performance, with further research on flexible stretchable electrodes it was applied to epidermal electronic devices and implantable electronic devices [49,50], which puts forward new requirements for flexible stretchable electrodes. To achieve a close skin fit, flexible stretchable materials need to have a lower Young's modulus (<260 kPa [51]) than the human epidermis.…”
Section: Functional Adjustmentmentioning
confidence: 99%
“…Similarly, Bharat Sharma et al [27] used Ag-NWs and CoNPs mixed solution spin coating method to modify silver nanowire networks wire-wire junctions with CoNPs to obtain AgNWs-CoNPs composite thin films with the best transmittance of 94% and the sheet resistance of 52 Ω/sq. Hu Yuehui et al reported [28] that the AgNWs-TCFs were obtained with a sheet resistance of 20 Ω/sq and uniform electrical properties by using the water mist method to make the silver nanowire networks wire-wire junctions in close contact through capillary force. However, the above-mentioned method of making silver nanowire networks wire-wire junctions in close contact still faces challenges in solving the degradation of electrical properties caused by the water-oxygen reaction of AgNWs-TCF in air.…”
Section: Introductionmentioning
confidence: 99%